1997
DOI: 10.1042/bj3250761
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization and purification of a p-hydroxyphenylpyruvate dioxygenase from cultured carrot cells and characterization of the corresponding cDNA

Abstract: p-Hydroxyphenylpyruvate dioxygenase catalyses the transformation of p-hydroxyphenylpyruvate into homogentisate. In plants this enzyme has a crucial role because homogentisate is the aromatic precursor of all prenylquinones. Furthermore this enzyme was recently identified as the molecular target for new families of potent herbicides. In this study we examine precisely the localization of p-hydroxyphenylpyruvate dioxygenase activity within carrot cells. Our results provide evidence that, in cultured carrot cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 34 publications
3
62
1
Order By: Relevance
“…Analysis of the M. truncatula genome sequence around the HPPD gene revealed that this legume species also has an N-terminal ORF extension that contains a predicted CTP. What is not clear is why Arabidopsis and some other nonlegumes would encode only cytosolic HPPD (Garcia et al, 1997(Garcia et al, , 1999. Perhaps the movement of homogentisate into the chloroplast serves as a regulatory step for the plastoquinone and tocopherol pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the M. truncatula genome sequence around the HPPD gene revealed that this legume species also has an N-terminal ORF extension that contains a predicted CTP. What is not clear is why Arabidopsis and some other nonlegumes would encode only cytosolic HPPD (Garcia et al, 1997(Garcia et al, , 1999. Perhaps the movement of homogentisate into the chloroplast serves as a regulatory step for the plastoquinone and tocopherol pathways.…”
Section: Discussionmentioning
confidence: 99%
“…HPPD was predicted to have a chloroplast-targeting peptide (CTP). Subcellular fractionation supported a cytosolic location of the carrot (Daucus carota) cell enzyme (Garcia et al, 1997). The same authors determined that after PSORT analysis failed to identify a targeting signal within the Arabidopsis (Arabidopsis thaliana) HPPD amino acid sequence, native Arabidopsis HPPD heterologously expressed in tobacco (Nicotiana benthamiana) was located exclusively in the cytosol (Garcia et al, 1999).…”
mentioning
confidence: 92%
“…Protoplasts were prepared by enzymatic digestion of 6-day-old cell suspension cultures, using the procedure described in ref. 21. Protoplasts were gently ruptured by passing through a 20-m nylon mesh and subsequently through a 10-m nylon mesh.…”
Section: Methodsmentioning
confidence: 99%
“…Genes and cDNAs encoding HPPDase have been identified from several mammalian, fungal, bacterial, and plant sources (Gershwin et al, 1987;Endo et al, 1992Endo et al, , 1995Hummel et al, 1992;Ruetschi et al, 1993;Coon et al, 1994;Denoya et al, 1994;Wilson et al, 1994;Wintermeyer et al, 1994;Kaneko et al, 1995;Wyckoff et al, 1995;Garcia et al, 1997) and show between 25% and 95% identity at the amino acid level. A computer search of the plant DNA databases, including 20,000 random Arabidopsis cDNAs (Newman et al, 1994), was conducted using human and bacterial HPPDase sequences as the query.…”
Section: Isolation and Characterization Of An Arabidopsis Hppdase Cdnamentioning
confidence: 99%
“…1). HPPDase is generally present at low levels in plant tissues and has only recently been purified to homogeneity from a plant source (Garcia et al, 1997).…”
mentioning
confidence: 99%